1992
DOI: 10.1128/iai.60.9.3682-3688.1992
|View full text |Cite
|
Sign up to set email alerts
|

Experimental model of intracerebral infection with Cryptococcus neoformans: roles of phagocytes and opsonization

Abstract: A murine model of intracerebral (i.c.) infection with Cryptococcus neoformans in which naive mice receiving an i.c. fungal inoculation developed a severe disease has been established. The effect was strictly dependent on the number of microorganisms injected and evolved as lethal meningoencephalitis. Murine susceptibility to i.c. infection with C. neoformans was enhanced by treatment with chloroquine and colchicine, agents known to greatly affect the host phagocytic compartment. Furthermore, the life spans of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 31 publications
1
34
0
Order By: Relevance
“…Since it is proposed that C. neoformans produces proteases, as biochemical devise(s) for nutritional recruitment [16,19], we suggest that such a pathway is critically disturbed upon exposure to the PI indinavir. By a murine model of experimental meningoencephalitis, it has been demonstrated that the brain phagocytic compartment is an important defence barrier against C. neoformans [27,[30][31][32]. Accordingly, in vitro studies reveal that microglial cells are endowed with direct antifungal activity and their efficacy may further increase, under appropriate conditions [27,28,33].…”
Section: Discussionmentioning
confidence: 99%
“…Since it is proposed that C. neoformans produces proteases, as biochemical devise(s) for nutritional recruitment [16,19], we suggest that such a pathway is critically disturbed upon exposure to the PI indinavir. By a murine model of experimental meningoencephalitis, it has been demonstrated that the brain phagocytic compartment is an important defence barrier against C. neoformans [27,[30][31][32]. Accordingly, in vitro studies reveal that microglial cells are endowed with direct antifungal activity and their efficacy may further increase, under appropriate conditions [27,28,33].…”
Section: Discussionmentioning
confidence: 99%
“…i.c. inoculations were performed on anesthetized mice, as previously described [11]. Brie£y, mice received the inoculum (30 Wl) into the brain, 1 mm lateral and posterior to the bregma, at a depth of 2 mm with a 0.1-ml microsyringe and a 27-gauge disposable needle.…”
Section: Intracerebral (Ic) Inoculationmentioning
confidence: 99%
“…Microglia may either allow C. neoformans intracellular survival and replication (Lee et al, 1995) or exert anticryptococcal activity, whose levels are enhanced upon exposure to IFN-g or chloroquine (Blasi et al, 1995b;Mazzolla et al, 1997;Saleppico et al, 1999). Furthermore, C. neoformans resistance to microglia is partially reduced by yeast cell preopsonization with fresh serum or by pretreatment with protease inhibitors (Blasi et al, 1992(Blasi et al, , 1995aLipovsky et al, 1997). Thus, both the early yeast-to-microglia recognition step(s) and the postphagocytosis intracellular events seem to be relevant in the outcome of such pathogen-host cell interplay.…”
Section: Introductionmentioning
confidence: 99%